2017
DOI: 10.1186/s12890-017-0441-3
|View full text |Cite
|
Sign up to set email alerts
|

Lung function development after preterm birth in relation to severity of Bronchopulmonary dysplasia

Abstract: BackgroundBronchopulmonary dysplasia (BPD) is a strong risk factor for respiratory morbidity in children born preterm. Our aims were to evaluate lung function in adolescents born preterm with and without a history of BPD, and to assess lung function change over time from school age.MethodsFifty-one individuals born in Stockholm, Sweden between gestational ages 24 to 31 weeks (23 neonatally diagnosed with respiratory distress syndrome (RDS) but not BPD, and 28 graded as mild (n = 17), moderate (n = 7) or severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 47 publications
(56 reference statements)
2
32
1
3
Order By: Relevance
“…Prior studies in extremely preterm children aged 3 to 7 years are limited. At school age (6–8 years of age), Um‐Bergström et al reported that FEV 1 and FVC z‐scores for severe BPD group was −2.6 and −2.2, respectively, and were similar to our findings for preschool‐aged children with severe BPD history. In addition, longitudinal comparison of spirometry between 7 and 14 years of age, Um‐Bergström et al reported significant increases of FVC with a very limited improvement of FEV 1 in adolescents with BPD history and lower FEV 1 values in adolescents significantly associated with BPD severity ( P for trend = 0.002).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Prior studies in extremely preterm children aged 3 to 7 years are limited. At school age (6–8 years of age), Um‐Bergström et al reported that FEV 1 and FVC z‐scores for severe BPD group was −2.6 and −2.2, respectively, and were similar to our findings for preschool‐aged children with severe BPD history. In addition, longitudinal comparison of spirometry between 7 and 14 years of age, Um‐Bergström et al reported significant increases of FVC with a very limited improvement of FEV 1 in adolescents with BPD history and lower FEV 1 values in adolescents significantly associated with BPD severity ( P for trend = 0.002).…”
Section: Discussioncontrasting
confidence: 99%
“…At school age (6–8 years of age), Um‐Bergström et al reported that FEV 1 and FVC z‐scores for severe BPD group was −2.6 and −2.2, respectively, and were similar to our findings for preschool‐aged children with severe BPD history. In addition, longitudinal comparison of spirometry between 7 and 14 years of age, Um‐Bergström et al reported significant increases of FVC with a very limited improvement of FEV 1 in adolescents with BPD history and lower FEV 1 values in adolescents significantly associated with BPD severity ( P for trend = 0.002). On the other hand, our findings were in contrary to those reported by Verheggen et al who found that the median FEV 1 and FVC z‐scores preterm children with BPD at 4 to 8 years of age were −0.59 and −0.26, respectively, and only FEV 1 z‐score was significantly lower than that of term control (0.49).…”
Section: Discussionmentioning
confidence: 99%
“…Same results were obtained in a similar cohort of 49 Finnish children studied at the age of 5-10 years 29 . Findings in adolescents born preterm between 24 and 31 weeks of gestation con rmed that those with a diagnosis of BPD had higher R5-R20 compared to peers without BPD 26 . In all the three studies FEV 1 was lower and often impaired in subjects with BPD.…”
Section: Populationmentioning
confidence: 83%
“…We speculate that the nding of lower FEF 25 − 75 in our cohort may re ect the impairment of small airways demonstrated with the increased values of the IOS indices. Previous studies showed concordant information between the oscillometric method and spirometry 26,28,29 but IOS is considered to be more sensitive in evaluating peripheral airways 13 . However, while we found a signi cant lower FEV 1 in subjects with BPD compared to those without BPD (-0.93 z-score), we did not nd a signi cant difference with IOS.…”
Section: Populationmentioning
confidence: 99%
See 1 more Smart Citation